2020
DOI: 10.1002/adma.202002702
|View full text |Cite
|
Sign up to set email alerts
|

Single‐Crystal SnSe Thermoelectric Fibers via Laser‐Induced Directional Crystallization: From 1D Fibers to Multidimensional Fabrics

Abstract: Single‐crystal tin selenide (SnSe), a record holder of high‐performance thermoelectric materials, enables high‐efficient interconversion between heat and electricity for power generation or refrigeration. However, the rigid bulky SnSe cannot satisfy the applications for flexible and wearable devices. Here, a method is demonstrated to achieve ultralong single‐crystal SnSe wire with rock‐salt structure and high thermoelectric performance with diameters from micro‐ to nanoscale. This method starts from thermally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
82
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 73 publications
(92 citation statements)
references
References 54 publications
0
82
0
Order By: Relevance
“…However complex in its cross-section, the fiber is typically axially uniform and needs to undergo application-specific post-processing if axial patterning is desired [5]. Keeping in mind that conventional preform techniques already result in a variety of non-trivial devices [6][7][8][9], and that the functional complexity of the device is directly linked to the fiber's structural complexity, one can imagine what a range of new possibilities a repeatable, digitized, and most importantly, free-form fabrication of preforms by 3D printing will open.…”
Section: Introductionmentioning
confidence: 99%
“…However complex in its cross-section, the fiber is typically axially uniform and needs to undergo application-specific post-processing if axial patterning is desired [5]. Keeping in mind that conventional preform techniques already result in a variety of non-trivial devices [6][7][8][9], and that the functional complexity of the device is directly linked to the fiber's structural complexity, one can imagine what a range of new possibilities a repeatable, digitized, and most importantly, free-form fabrication of preforms by 3D printing will open.…”
Section: Introductionmentioning
confidence: 99%
“…Although the high uniformity along the fiber axial 5 Advanced Devices & Instrumentation direction is a magnificent advantage of thermally drawn fibers to ensure reliable production and stable performance, it also brings some limitations in certain applications where localized information along the fiber is needed, or multiple functional units are needed to be integrated along the fiber axial direction. Therefore, to make full use of the fiber length, [70][71][72], laser recrystallization [73], cold drawing [74], and convergence thermal drawing [75]. Kaufman et al reported a postprocessing approach to introduce Plateau-Rayleigh instability for breaking the axial symmetry of thermally drawn fibers [71].…”
Section: Breaking the Axial Symmetry Of Thermally Drawn Fibersmentioning
confidence: 99%
“…A clear rectifying current-voltage (IV) curve is measured to reveal their stable contact, showing the perspective of the in-fiber assembly of 3D functional structures. Also, the crystal structure of the fiber core could be engineered by the laser beam [73]. As sketched in Figure 4(d), a thermoelectric material tin selenide (SnSe) core in a thermally drawn fiber is successfully recrystallized by CO 2 laser annealing from as-drawn polycrystalline to single crystalline.…”
Section: Advanced Devices and Instrumentationmentioning
confidence: 99%
“…Prototypes of miniatured modules consisting of up to four uni-couples composed of p-type Bi 0.5 Sb 1.5 Te 3 and n-type Bi 2 Te 2.7 Se 0.3 sintered fibers are displayed in Figure 1 h. As a result, the as-extruded fibers were very flexible and could be formed into various shapes, which can be used in various applications of portable and wearable devices (inset of Figure 1 h) [ 30 ]. Moreover, a single bendable thermoelectric fiber was formed from the nanoscale to microscale ( Figure 1 j) through thermal drawing process [ 31 ], which was specified by continuously pulling microscopic fibers from a macroscopic preform in a controllable manner; this technique usually requires that the Tg (glass transition temperature) of the cladding materials needs to be higher than the Tm (melting point) of the functional core materials. Through regulating the preform feeding and the fiber drawing speed, the fiber core diameter can be controlled within a wide range (from tens of nanometers to several millimeters) and the built-in stress between the cladding and core materials induced by the mismatch of thermal expansion coefficients can be optimized.…”
Section: Inorganic Synthetic Fibersmentioning
confidence: 99%
“…( d ) Demonstrations of multidimensional SnSe fabric for converting heat to electricity. Reproduced with permission [ 31 ]. Copyright 2020, Wiley.…”
Section: Figurementioning
confidence: 99%